Opinion 2452: Geophilus bonensis Meinert, 1870 (Chilopoda): specific name not conserved - ICZN (Bulletin of Zoological Nomenclature, 2020)
The International Commission on Zoological Nomenclature has declined to use its plenary power to conserve the specific name of Geophilus bonensis Meinert, 1870 (currently Gnathoribautia bonensis) for a species of geophilomorph centipede. As a result, the name punctiventris Newport, 1844, as published in the binomen Necrophloeophagus punctiventris, has priority over the name bonensis Meinert, 1870, as published in the binomen Geophilus bonensis, whenever they are considered synonyms.
Keywords: Nomenclature; taxonomy; Chilopoda; Gnathoribautia; Geophilus bonensis; Necrophloeophagus punctiventris; Arthronomalus mandibularis; Arthronomalus punctatus; Geophilus hirsutus; geophilomorph centipedes